Assessment of Development Results - Bangladesh - United Nations Development Programme (United Nations, 2011)
This report presents an independent evaluation managed by the Evaluation Office of the United Nations Development Programme (UNDP) in Bangladesh in 2010. It assesses UNDP’s overall contribution to the development of the country over the most recent programming cycles, as well as the strategy and performance of UNDP-Bangladesh during the last programme cycles and their action plans.